Pengaruh Beban Kerja, Lingkungan Dan Pengembangan Karir Terhadap Kepuasan Kerja Karyawan Di Sthala, A Tribute Portfolio Hotel - Ni Kadek Kisnayanti; Made Yudi Darmita; Ni Luh Komang Julyanti Paramita Sari (Universitas Triatma Mulya, 2025)
Job satisfaction is an emotional state where the value of employee remuneration for the company or organization meets the value of remuneration desired by the employee. This study examines the effect of workload (X1), work environment (X2), and career development (X3) on employee job satisfaction (Y). The population in this study was 79 people. The sampling technique in this study used the census method. The data analysis techniques used were descriptive analysis, data instrument testing, classical assumption testing, multiple linear analysis, t-test analysis, and beta coefficient analysis. The results of the analysis showed a regression model of Y = 5.063 + 0.250 X1 + 0.138 X2 + 0.270 X3. The conclusion obtained is that workload (X1) has a positive and significant effect on employee job satisfaction (Y) at Sthala, A Tribute Portfolio Hotel, Ubud Bali, as indicated by the regression coefficient b1X1 which has a positive and significant value of 0.005 <0.05. The work environment (X2) has a positive and significant effect on employee job satisfaction (Y) at Sthala, A Tribute Portfolio Hotel, Ubud, Bali. This can be seen from the positive b2X2 coefficient and a significance level of 0.001 <0.05. Career development (X3) has a positive and significant effect on employee job satisfaction (Y) at Sthala, A Tribute Portfolio Hotel, Ubud, Bali. This can be seen from the positive b3X3 coefficient and a significance level of 0.000 <0.05. The independent variable that has a dominant influence on employee job satisfaction, as seen from the Standardized Coefficients Beta value, is the workload variable (X1), which is 0.346.